Ovarian Cysts in Menopausal Women (Literature Review) - S. F. Taychinova; Sh. Kh. Gantsev; A. Z. Mullagalina; G. R. Akberdina (Креативная хирургия и онкология, 2019)
Introduction. The incidence of ovarian cyst amounts to 5–17 % in postmenopausal women. Currently monitoring of or screening for ovarian cysts in menopausal patients is not regimented in the Russian Federation at all. This situation warrants a review.Materials and methods. In this paper the authors review retrospective and prospective studies concerning outcomes in patients with ovarian cysts in menopause published in the last 5 years. Results. The retrospective and prospective studies analysed show that the risk of malignancy of this type of benign neoplasm is low, on average 0.7%. The results of a large prospective study prove that there is no need for surgical treatment in 80% of patients.Discussion. There is now doubt that patients with this disorder should be followed up in accordance with an algorithm that clearly defines the criteria for surgical treatment and the follow up length. Surgical treatment should be indicated when there is at least one of the signs of an ovarian cyst: symptomatic, texture not smooth, over 50 mm in diameter, multilocular, bilateral. A positive CA-125 in combination with ultrasound, MRI and CT imaging make it possible to calculate the risk index with the use of a particular formula and determine the indications for a risk-reducing bilateral salpingo-oophorectomy. The follow up of BRCA1/2 mutation-free patients with a benign ovarian neoplasm should include a close step-by-step monitoring and all the necessary examinations performed in a timely manner.Conclusion. The risk of a malignant transformation of an ovarian cyst in menopause is rather low (about 0.7%); following up patients with simple ovarian cysts in menopause is possible and should be carried out in strict compliance with the algorithm; the preventive bilateral salpingo-oophorectomy in patients presenting no signs of ovarian pathology is indicated only for the high risk group (BRCA1/2 mutations confirmed or there is family history).